Torta de gergelim na alimentação de frangos de corte - Primo, Amanda Peregrine (2008)
The sesame cake has high protein contents and can be used on human and animal diets. Broiler industry has been concentrating its attention on the high income of carcass and the protein supplied on diets influence directly on feed conversion, quality of carcass and broilers weight gain. So, this study aimed at evaluating the performance and yield of broilers carcass, when soybean meal was replaced by sesame cake. Considering four different diets compared with the control one (0% sesame cake), in each broilers development phase, since there is a specific diet for each phase. The experimental treatments were: control diet (0% sesame cake), 25% of sesame cake in replacement of soybean meal; 50% of substitution; 75% of substitution; and 100% of substitution (only sesame cake). The substitutions phases were: pre-initial (1 to 7 days), initial (8 to 21 days), growth (22 a 35 days) and final phase (36 a 46 days). A total of 750 male Cobb chicks of one day were used. There were five replications per treatment, with 30 broilers in each repetition. The broilers were housed in wooden boxes with wire netting in a randomized sampling distribution with 10 birds by repetition. The floor was covered with hens litter material, re-used for the fourth time. Hens and diets were weighed weekly. At 46 days, the hens were slaughtered in an industrial plant of broilers, in order to evaluate the carcass income and its parts. Data were analyzed at each change of diet, to get the models and weekly to valuation. These data were submitted to the analysis of variance and the averages were compared by Tukey test at 5% of significance. It was observed that the substitution of soybean by sesame cake increased the hens performance and their income of carcass, but it did not increase the diet consumption nor the abdominal fat rate. In the studied conditions, it was recorded that the weight and the diet consumption models were linear and the feed conversion model was polynomial. Moreover, the substitution of soybean for sesame cake was viable from 50% on broilers diet.